Analysis of Factors Affecting Export and Import Performance - Adela Nursafira; Annisa Syafriani; Sabrina Natasya Matondang; Dayu Rizki Nurhamda; Dwita Sakuntala (Indonesian Journal of Entrepreneurship and Startups, 2025)
Exports and imports are essential elements of international trade that influence a country's economic growth. This article aims to analyze in-depth the factors affecting Indonesia's export and import performance between 2020 and 2024. The research method used is descriptive qualitative, with data collection through interviews with business actors, literature studies, and analysis of official documents. Indonesia's exports are influenced by product quality, government policies, global economic conditions, exchange rates, and infrastructure, while imports are related to domestic needs, international prices, government policies, and supporting infrastructure. The decline in exports in 2020 was caused by the impact of the COVID-19 pandemic; however, the export sector began to recover in 2021-2022 due to rising commodity prices. In early 2024, exports declined again due to global price fluctuations, reduced demand from China, and global geopolitical uncertainties. On the import side, despite a decline in May 2024, high demand for raw materials and capital goods remained, particularly in the industrial sector. Indonesia's trade performance shows a complex dynamic, influenced by both domestic and global factors. Therefore, there is a need for export product diversification, strengthening the manufacturing sector, improving international trade cooperation, and innovation in global marketing strategies to make Indonesia more competitive. Additionally, the development of logistics infrastructure and digital transformation should be prioritized to support trade efficiency.